2008
DOI: 10.1677/joe-08-0380
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of endocannabinoid anandamide and CB1 receptor antagonist, AM251 in the regulation of thyrotropin secretion

Abstract: We examined the acute effects of endocannabinoid, anandamide, and of synthetic cannabinoid receptor antagonist, AM251[N-(piperidin-1-yl)-1-(2,4-dichlorophenyl)-5-(4-chlorophenyl)-4-methyl-1H-pyrazole-3-carboxamide], on TSH, thyroxine (T 4 ), and triiodothyronine (T 3 ) secretions. Euthyroid male rats showed a 42% decrease in serum TSH, 2 h after a single i.p. injection of 0 . 02, but not 0 . 2 mg/kg body weight (BW), anandamide, accompanied by a 39% reduction in serum T 4 , without alteration in serum T 3 . At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…32 Studies suggest that endocannabinoids have a negative regulation on TSH, T3 and T4 secretions. 32,61,62 In addition, FAAH knockout mice had significant TSH, T 3 and T 4 reductions. 63 In a previous work, we demonstrated that NIC males showed low TSH, T 3 and T 4 plasma levels, while NIC females had higher T 3 and T 4 .…”
Section: Discussionmentioning
confidence: 99%
“…32 Studies suggest that endocannabinoids have a negative regulation on TSH, T3 and T4 secretions. 32,61,62 In addition, FAAH knockout mice had significant TSH, T 3 and T 4 reductions. 63 In a previous work, we demonstrated that NIC males showed low TSH, T 3 and T 4 plasma levels, while NIC females had higher T 3 and T 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Administration of AEA led to an acute decrease in TSH and T4, but not T3 levels in rat serum, while application of CB1 inverse agonists acutely raised TSH levels [ 362 ]. These findings are overall in line with previous reports showing that THC reduces serum TSH, T4 and T3 [ 363 ], while the synthetic CB1/CB2 agonist WIN 55212-2 reduced T4 and T3, but did not alter TSH levels [ 364 ].…”
Section: Endocannabinoids In Peripheral Body Weight Controlmentioning
confidence: 99%
“…It is interesting in this regard that glucocorticoid-induced mobilization of ECS has been shown to inhibit glutamate release onto TRH-positive neurons in the hypothalamus (Di et al, 2003), suggesting that eCBs link stress and suppression of the HPT axis. Cannabinoids have also been shown to suppress the HPT axis at the pituitary (Veiga et al, 2008) and thyroid gland (Porcella et al, 2002). However, inhibition at the first step in a cascade such as the HPT axis will have the greatest impact in vivo .…”
Section: Interaction Of Cannabinoids With Hormonal Regulation Of Growmentioning
confidence: 99%